Psychological aspects in the sport preparation of Brazilian woman gymnasts: The partizipating in the Olympic Games: The gymnast's view - Marconi Schiavon, L. (High performance gymnastics, 2014)
The testimonies presented in this chapter may not portray the brazilian reality as a whole, therefore, they can't be generalized. However, they represent the conditions of the ten most outstanding female gymnasts in Brazil from 1980 to 2004, from their own perspective, providing the sport professionals with reflections related to the directions in artistic gymnastics, so that it can be an excellence modality in Brazil not only with regard to the results, but to the process adopted for training the gymnasts.